(3GdMeGjI GdJTQjYjI GdeOfjI hGdLfGFjI dHWGbGJ GdOaY GdGdjcJQhfis (3HWGbGJ GdGFJeGfs - (3GHQGgje(B, (3SjO CMeOs ((3GdGScfOQjIs (3GdOGQ GdLGeYjIs, 2005)
(3JYQja HWGbGJ GdGFJeGf, hLhH JfajO GdGdJRGe, GdLRGA dYOe JfajO GdGdJRGe, eUWdM HWGbI GdGFJeGf, CfhGY hWHjYI GdGFJeGf hMeGjJgG ef GdfGMjI GdeOfjI, GdMeGjI GdLfGFjI dHWGbGJ GdOaY GdGdjcJQhfj, eGgjI heaghe GdMeGjI, aj eLGd heQMdI GdJYGbO, aj eLGd heQMdI JfajP GdYbO, GdBKGQ GdeJQJHI Ydi GLJeGY GdeSDhdjJjf GdeOfjI hGdLfGFjI, MLjI GdMce GdLfGFj GdUGOQ HGdHQGAI, GdCMcGe GdYGeI dLQjeI GdJRhjQ hGdMce GdLfGFj HTCfgG(B.s
Keywords: (3GdJTQjY(B-(3bhGfjfs; (3GdeUGQa(B- (3bhGfjf hCfXeIs; (3HWGbGJ GdGFJeGfs